Christian supremacy: reckoning with the roots of antisemitism and racism - Teter, Magda (Princeton University Press, 2023)
"Appalling events in recent years have brought home to us the pervasiveness of white supremacist views, practices, and structures in both the United States and in Europe. This stunningly ambitious, sweeping cultural and intellectual history explores their Christian origins. It also argues for the enduring importance of these origins -- even if contemporary white supremacists do not always rely on explicitly religious rationales for their ideas. Magda Teter's book traces modern day anti-Jewish and anti-Black prejudice back to pervasive notions of Christian superiority developed in the early Christian church. She thus connects anti-Jewish sentiments with anti-Black racism, without arguing that these are the same thing or that one led to the other. Based on an examination of primary evidence across a wide geographical and historical array of sources-theological, legal, artistic, and philosophical-Teter shows how the Christian claim of superiority emerged in a theological context in antiquity and was later implemented in a legal and political context when Christianity became a political power. And in the early modern era, when Europeans expanded their political reach beyond Europe with the establishment of commerce-driven slaveholding empires, Christian claims were transformed decisively into a racialized sense of superiority that became institutionalized in law and politics"--